Serum albumin measurement in nephrology: room for improvement. Issue 10 (24th December 2020) - van Schrojenstein Lantman, Marith; van de Logt, Anne-Els; Thelen, Marc; Wetzels, Jack F; van Berkel, Miranda
Abstract: Serum albumin is a widely used biomarker in clinical nephrology. Serum albumin cut-off values are used to define disease, to predict outcome and to guide patient care. The available commercial assays to measure serum albumin rely on different analytical principles, all with their own (analytical) specifications. This article provides an overview of the different clinical applications of serum albumin measurements in nephrology, the (dis)advantages of the available assays and the estimates of the effects of the measurement uncertainty between different assays in clinical decision making. This article concludes that harmonization of serum albumin assay results is needed.